Psychological Projection: Trump and Santos (Birds of a Feather Flock Together, What Every U.S. Voter Should Know) - Levenson, Harvey R. (Advances in Social Sciences Research Journal, 2024)
There has been a tremendous amount of media coverage regarding former President Donald Trump, and his rhetoric concerning a second run at winning the White House. There has been much speculation about his motives and appeals to his base. Trump’s rhetoric has become the focus of study amongst scholars in the areas of communication, political science, psychology, sociology, and even psychiatry. For example, there has been a lot of speculation that his motivation has been triggered by anger, retribution, and his own perception that he is right and all those judging him, including the courts, are wrong. When this research was started, there was no consideration given to including an assessment of the character of former Representative George Santos (R. NY), and his similarities to Trump in thinking and behavior. However, as the Santos case unfolded, and his allegiance to Trump, there appeared similarities that could help explain the behaviors of others supporting Trump and the MAGA movement, and what might be lying ahead if the United States supports a second Trump presidency. There is one explanation occasionally covered by the media, but not in the detail that Trump’s base and the general public would understand. The explanation is the psychological phenomenon known as “projection.” This paper attempts to explain this phenomenon in a way that would be understood by the average voter to help decide if the “projection” should be considered in selecting Trump as the Republican Party 2024 presidential choice in the primaries and in the general election. This paper explains the phenomenon of projection and how it is practiced specifically by Trump and Santos, and offers a few solutions for addressing and correcting this psychological ailment.